2012
DOI: 10.1016/j.jmbbm.2012.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Simulated bone remodeling around two types of osseointegrated implants for direct fixation of upper-leg prostheses

Abstract: Direct attachment of an upper leg prosthesis to the skeletal system by a percutaneous implant is an alternative solution to the traditional socket fixation. In this study, we investigated long-term periprosthetic bone changes around two types of fixation implants using two different initial conditions, namely immediate post-amputation implantation and the conventional implantation after considerable time of socket prosthesis use. We questioned the difference in bone modeling response the implants provoked and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
54
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 49 publications
3
54
1
Order By: Relevance
“…This is in agreement with a radiographic follow‐up of a patient cohort, where no bone resorption was observed in the zones distal to the implant, as well as no cortical thinning in this zone in the majority of cases . Further, this distal zone has not been considered in previous modeling of the implant system, where no countersinking of the implant was present which is likely to change the overall distribution of loads significantly, as the lever arm is lengthened, thereby altering the moment in flexion. The clinically retrieved sample in the current study showed a preserved bone height at distal level after 15 years in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with a radiographic follow‐up of a patient cohort, where no bone resorption was observed in the zones distal to the implant, as well as no cortical thinning in this zone in the majority of cases . Further, this distal zone has not been considered in previous modeling of the implant system, where no countersinking of the implant was present which is likely to change the overall distribution of loads significantly, as the lever arm is lengthened, thereby altering the moment in flexion. The clinically retrieved sample in the current study showed a preserved bone height at distal level after 15 years in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…To meet the existing challenges faced by DSA, the development of new designs and methodologies for reducing the associated risks continues. New challenges may arise with the promising use of the transcutaneous implants for neuromuscular control of the limb prostheses .…”
Section: Discussionmentioning
confidence: 99%
“…22,24,87,92 An additional concern for longevity of the bone-device bond is that after replacement surgery, the porosity of the cortical bone hosting the femur implant increases compared to the ipsilateral bone, potentially reducing cortical bone strength. 93,94 To meet the existing challenges faced by DSA, the development of new designs and methodologies for reducing the associated risks 95,96 continues. New challenges may arise with the promising use of the transcutaneous implants for neuromuscular control of the limb prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures do not have the same socket‐related soft tissue issues, facilitate quick attachment of the amputee's prosthesis, transfer load directly to the residual femur, and enable osseoperception whereby the amputee can discern the type of surface they are walking on . Downsides to direct skeletal attachment include a risk of superficial and deep infection through the skin opening, a risk of femoral fractures, implant extraction, high proximal revision, and potential bone resorption due to stress shielding . Despite the variety of devices, it appears that many surgeons remain unhappy with the concept of a permanent percutaneous implant.…”
mentioning
confidence: 99%
“…6 Downsides to direct skeletal attachment include a risk of superficial and deep infection through the skin opening, a risk of femoral fractures, implant extraction, high proximal revision, and potential bone resorption due to stress shielding. [13][14][15][16] Despite the variety of devices, it appears that many surgeons remain unhappy with the concept of a permanent percutaneous implant. Subcutaneous implants have been developed: in the 1960s Swanson et al 17 developed a mushroom-shaped silicone implant in an attempt to improve end bearing.…”
mentioning
confidence: 99%